Knowing the other/other ways of knowing: Indigenous feminism, testimonial, and anti-globalization street discourse. (February 2017) - Dulfano, Isabel
In this article, I explore the relationship between anti-globalization counter hegemonic discourse and Indigenous feminist alternative knowledge production. Although seemingly unrelated, the autoethnographic writing of some Indigenous feminists from Latin America questions the assumptions and presuppositions of Western development models and globalization, while asserting an identity as contemporary Indigenous activist women. Drawing on the central ideas developed in the book Indigenous Feminist Narratives: I/We: Wo(men) of An(Other) Way, I reflect on parallels and counterpoints between the voices from the global street movement, "other" epistemologies (identified hereafter), postcolonial theory, and contemporary Indigenous feminist theorization.